Process-integrated steel ladle monitoring, based on infrared imaging – a robust approach to avoid ladle breakout. Issue 3 (2nd July 2020) - Chakraborty, Biswajit; Sinha, Billol Kumar
ABSTRACT: Ladle breakout is a risky affair which is always present in steel making. The ladle breakout involves equipment damage and loss of production and sometimes loss of life. The present article describes the method of automatic detection of hotspot on the cold side of a ladle shell with the help of a group of infrared camera and subsequent processing of the infrared images in the LabVIEW platform. The system layout as implemented in the steel plant along with various pitfalls likely to be encountered during operation is discussed. Finally, the result of the trial run in the steel plant is presented. The system is found to be very effective as a preventive maintenance program to stop or minimise the ladle breakout.